1950
DOI: 10.1146/annurev.pp.01.060150.000545
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Sugars in Plants

Abstract: The first sugar of photosynthesis.-Glucose, fructose, sucrose, and starch are formed in green plants as a result of photosynthetic activity and can easily be detected. Because of this, plant physiologists devoted considerable effort for over half a century to prove which of these carbohydrates consti tutes the "first sugar of photosynthesis." Their experimental approach was to determine the relative concentrations of these carbohydrates in the plant at different times of the day and seasons of the year and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1951
1951
1983
1983

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…A similar interpretation was proposed by CHRISTIANSEN and THIMANN (5) for the decrease in sucrose without a decrease in reducing sugars in sections of pea stems cultured in a mediumii containing auxin. Though other interpretations such as the partial conversion of the disaccharide to reducing sugars are possible, a preferential utilization of sucrose in the first stages of growth could be explained by the possibility that it undergoes phosphorolysis, yielding highly active hexose phosphate, and by its higher energy content (7,11,33).…”
Section: Discussionmentioning
confidence: 99%
“…A similar interpretation was proposed by CHRISTIANSEN and THIMANN (5) for the decrease in sucrose without a decrease in reducing sugars in sections of pea stems cultured in a mediumii containing auxin. Though other interpretations such as the partial conversion of the disaccharide to reducing sugars are possible, a preferential utilization of sucrose in the first stages of growth could be explained by the possibility that it undergoes phosphorolysis, yielding highly active hexose phosphate, and by its higher energy content (7,11,33).…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium constant of reaction la in the direction of sucrose-P synthesis has been reported to be 3250 at 38 C and pH 7.5 (11). When this reaction is coupled with sucrose phosphatase, the biosynthesis of sucrose can be considered essentially irreversible.…”
Section: Hoursmentioning
confidence: 99%
“…Despite its considerable conversion to pectic substance, virtually none of the 14C in myo-inositol was incorporated into TA. It has already been reported that [6-"4C]glucuronate is a very poor precursor of AA in plants (16,19), and that free glucuronate does not occur in plants under normal conditions (10). It is also known that glucuronate is in equilibrium with glucurono-y-lactone in solution, and that the equilibrium shifts to the direction of lactone formation under acidic conditions which prevail in the berry (6).…”
mentioning
confidence: 99%